2019
DOI: 10.1163/15685306-00001902
|View full text |Cite
|
Sign up to set email alerts
|

How Prevalent Are Invertebrates in Human-Animal Scholarship? Scoping Study of Anthrozoös and Society & Animals

Abstract: The field of Human-Animal Studies (HAS) is about human-animal relations. However, which nonhuman animals does the field encompass? In recent years, some scholars have noted a bias towards vertebrate species, especially domesticated mammals. To assess how prevalent (or not) invertebrates have been in HAS scholarship, a three-stage scoping study was conducted of two pioneering journals in the field: Anthrozoös and Society & Animals. This article reports on preliminary findings and confirms that human-animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The relatively low number of studies included and species represented in the research identified for this review reinforces the assertion made by Wilkie and Moore [7] that human-animal research overwhelmingly studies specific animals, such as vertebrates and mammals, to the exclusion of others. Furthermore, exactly which species are included in companion animal studies can be difficult to ascertain because animals other than cats and dogs are often reported in a category labelled only as "other" [39].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The relatively low number of studies included and species represented in the research identified for this review reinforces the assertion made by Wilkie and Moore [7] that human-animal research overwhelmingly studies specific animals, such as vertebrates and mammals, to the exclusion of others. Furthermore, exactly which species are included in companion animal studies can be difficult to ascertain because animals other than cats and dogs are often reported in a category labelled only as "other" [39].…”
Section: Discussionsupporting
confidence: 69%
“…Seven overarching themes describe the possible processes or mechanisms by which companion animals may benefit their human guardians' health: (1) Companionship and Attachment, (2) Social Facilitators, (3) Purpose and Routine, (4) Connectedness with nature, (5) Decoration and Aesthetics, and (6) Physiological Benefits. There was an additional theme for (7) Commercial Media, in which human health benefits of companion animals were discussed in non-scientific contexts, and explanatory mechanisms of health benefits were not evident. Participants described varying levels of attachment to companion reptiles, ranging to "like" and "love".…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though ethical discourse is useful, animal welfare regulations should be based on evidence-based findings rather than popular mediaconstructed and often anthropomorphised narratives. Nevertheless, there is certainly a research bias towards domesticated mammalian vertebrates [60].…”
Section: Influence Of Animals In Filmed Mediamentioning
confidence: 99%